Ignition delay time and sooting propensity of a kerosene aviation jet fuel and its derivative blended with a bio-jet fuel. (15th November 2018) - Han, Hee Sun; Kim, Chul Jin; Cho, Cheon Hyeon; Sohn, Chae Hoon; Han, Jeongsik
Abstract: Ignition delay time and sooting index of kerosene blended with a bio-jet fuel is measured for a comparative study with general aviation fuels. The new blended fuel is similar to a kerosene jet fuel (Jet A-1 or Korean domestic jet fuel) in terms of properties, H/C ratio, density, and heat of combustion. But, its ignition characteristics and sooting propensity are different from those of Jet A-1. Ignition delay time is measured by a shock tube and it is found that the blended fuel of kerosene and a bio-jet fuel has NTC (negative temperature coefficient) behavior. Ignition delay times of the blended fuel are compared with those of jet fuels (Jet A-1 and Jet A) over a wide range of temperature from 700 K to 1200 K at 20 atm. The blended fuel has shorter ignition delay time at low temperature below 900 K. It can be explained by short ignition delay of components in a bio-jet fuel at low temperature. In terms of sooting propensity, blending with a bio-jet fuel reduces the propensity remarkably to a half.